THE ROLE OF CHATGPT IN RADIATION ONCOLOGY: A LITERATURE REVIEW - Adikaraputri, Elita Verina; Rafiq Sulistyo Nugroho; Alfred Julius Petrarizky; Farel Muhammad Sayyaf Haydar; Satya Alfarisma Panggabean (Department of Radiology, Medical Faculty, University of Brawijaya, 2026)
Background: Artificial Intelligence, such as ChatGPT, is generating significant attention in the current age of personalized medicine. Considering the role of AI in synthesizing information and providing recommendations, this literature review examines the role and potential applications of AI language models in educational settings, medical decision-making, patient communication, and research for radiation oncologists and medical students. Methods: This literature review was developed based on the role ChatGPT-3.5 and ChatGPT-4 in addressing case scenarios related to radiation oncology from Google Scholar, PubMed, and ScienceDirect databases. The main keywords are “ChatGPT” and “Radiation Oncology”. This searching process results in ten valid and reliable articles. Results: The findings suggest that the responses generated by ChatGPT were valid and comparable to the professional proficiency of experts in radiation oncology, specifically for assisting in patient queries, information and decision maker provision, summarizing radiology reports for patients, and facilitating research related to radiation oncology. Nevertheless, ChatGPT has limitations and cannot substitute the role of a doctor under any circumstances. Conclusion: ChatGPT has a proven role and potential as a learning platform for healthcare practitioners specializing in radiation oncology. In addition, ChatGPT can deliver information to patients regarding their complaints. However, ChatGPT-3.5 and ChatGPT-4 still have limitations that need to be addressed to improve their performance.